Genetic diseases in the Jewish population - Risch, Neil (Henry Stewart Talks, 2007)
Jewish history and genetics, Classification of Jews, Genetic diseases found in Jews, particularly Ashkenazi Jews, Lysosomal storage diseases, Natural selection (heterozygote advantage) vs. genetic drift, Mutation frequencies, ages and geographic distributions, Bottlenecks in Jewish history